2016
DOI: 10.1039/c6ra07666a
|View full text |Cite
|
Sign up to set email alerts
|

Light upconverting soft particles: triplet–triplet annihilation in the phospholipid bilayer of self-assembled vesicles

Abstract: Large unilamellar vesicles (100 nm) were functionalised to obtain supramolecular particles capable of light upconversion in pure aqueous media. Triplet-triplet annihilation of diphenylanthracene (DPA) leading to delayed fluorescence at 420 nm was used to upconvert the light absorbed by embedded metal complex sensitisers. The lipid type and the chromophore position in the membrane affect the TTA intensity, which remains constant over a large concentration range. 941 943 1717; Tel: +49 941 943 4575 † Electronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 24 publications
1
14
0
Order By: Relevance
“…The need to extend this phenomenon to water environment and to biological specimen triggered remarkable efforts in the preparation of TTA‐UC structures. Among them, active polymeric structures, ionogels, liposomes, different supramolecular approaches, oil in water microemulsions, dendrimers, micelles, and water dispersible nanoparticles and nanocapsules led to demonstration of the applicability of TTA‐UC both in vitro and in vivo, within the tissue transparency window …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The need to extend this phenomenon to water environment and to biological specimen triggered remarkable efforts in the preparation of TTA‐UC structures. Among them, active polymeric structures, ionogels, liposomes, different supramolecular approaches, oil in water microemulsions, dendrimers, micelles, and water dispersible nanoparticles and nanocapsules led to demonstration of the applicability of TTA‐UC both in vitro and in vivo, within the tissue transparency window …”
Section: Introductionmentioning
confidence: 99%
“…Very recently Yanai and co‐workers demonstrated that the synthesis and water phase self‐assembly of amphiphilic cationic acceptor molecules with anionic donor (sensitizer) molecules provides an efficient way to address the oxygen quenching issue by a purely supramolecular approach . Finally, König and co‐workers demonstrated efficient TTA‐UC in large unilamellar vesicles loaded with suitably functionalized diphenylanthracene derivatives as well as both PtOEP and a Ru bipyridine complex . Unfortunately, all of the aforementioned approaches require either the synthesis of specifically designed chromophores, the incorporation of organic solvents, or a complex multistep fabrication of appropriate nanovectors, and therefore they can be impractical in many cases.…”
Section: Introductionmentioning
confidence: 99%
“…This way the sensitizer and annihilator are used more optimally while at the same time the energy transfer rates are increased due to the dense packing of the chromophores. Several examples exist and range from lipid bilayers [59][60][61] to using DNA as an assembly scaffold [62] . Associated to this is also encapsulation of the TTA-UC system into protective environments with the intent to be used in polar solvents like water which would increase the usability of TTA-UC in real life applications.…”
Section: Soft Systemsmentioning
confidence: 99%
“…29,30,32,33 However, the essential requirements for TTA-UC, i.e., triplet energy transfer and annihilation processes, rely on the molecular diffusion of TTA-UC dyes ( Figure S3, Supporting Information), which are inevitably suppressed in these viscous environments. 32,33 The hydrophobic interior of aqueous micelles 34 and lipid membranes [35][36][37][38] has also been employed to dissolve hydrophobic TTA-UC dyes, where the similarly limited diffusion of chromophores in the interior of these molecular assemblies limits their performance.…”
Section: Introductionmentioning
confidence: 99%